Oxidation of aniline over titania pillared montmorillonite clays - Jagtap, Neelam; Ramaswamy, Veda (Applied Clay Science, 2006)
Titania pillared clays (Ti-PILC) have been synthesized employing conventional stirring (method I) and ultrasonic agitation (method II) techniques followed by hydrothermal treatment. The characterization results revealed the formation of Ti-PILC with significant reduction of time when ultrasonic method was used. Subsequent hydrothermal treatment on the samples has resulted in the increase in the crystallinity and the transformation of anatase TiO2 to rutile TiO2. The rutile phase is more prominent in the samples prepared by stirring method. UV-Vis studies on the samples exhibit blue shift in the absorption band due to the quantum size effect. This indicates that a major part of TiO2 in the pillared clay could be well below 10 nm in size, which is supported by XRD and the average pore size. The pillared clay catalysts have proved to be promising in aniline oxidation with H2O2, selectively forming azoxybenzene under the working conditions. The aniline conversion and the product distribution largely depended on the catalyst concentration, H2O2 to aniline mole ratio, the nature of the solvent and the oxidant. Higher conversion of aniline and greater selectivity for azoxybenzene was obtained with methanol as the solvent. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: aniline oxidation; Azoxybenzene; hydrothermal treatment; pillared clays

Ozone assisted autohydrolysis of wheat bran enhances xylooligosaccharide production with low generation of inhibitor compounds: a comparative study - Sonkar, Rutuja Murlidhar; Gade, Pravin Savata; Bokade, Vijay; Mudliar, Sandeep N.; Bhatt, Praveena (Bioresource Technology, 2021)
In the present study, ozone assisted autohydrolysis (OAAH) was evaluated for enhanced generation of xylooligosaccharide (XOS) from wheat bran. The total XOS yield with optimum ozone dose of 3% (OAAH-3) was found to be 8.9% (w/w biomass) at 110 degrees C in comparison to 7.96% at 170 degrees C by autohydrolysis (AH) alone. Although, there was no significant difference in oligomeric composition (DP 2-6), significant decrease in degradation products namely furfural (2.78-fold), HMF (3.15-fold), acrylamide (nil) and acetic acid (1.06-fold), was observed with OAAH-3 as a pretreatment option. There was 1-fold higher xylan to XOS conversion and OAAH-hydrolysate had higher DPPH radical scavenging activity than AH. PCA plots indicated clear enhancement in XOS production and lower generation of inhibitors with decrease in treatment temperature. Results of the study therefore suggest OAAH can be an effective pretreatment option that can further be integrated with downstream processing for concentration and purification of XOS.
Keywords: Advanced oxidation; Agro-industry waste; hydrothermal treatment; Ozonolysis; Xylooligosaccharide